Microbiology of healthcare-associated infections and the definition accuracy to predict infection by potentially drug resistant pathogens: a systematic review - Cardoso, T. (2015)
Healthcare-associated infections (HCAI) represent up to 50 % of all infections among patients admitted from the community. The current review intends to provide a systematic review on the microbiological profile involved in HCAI, to compare it with community-acquired (CAI) and hospital-acquired infections (HAI) and to evaluate the definition accuracy to predict infection by potentially drug resistant pathogens.